Estudo clínico-patológico do carcinoma epidermóide de língua e imunoistoquímico das proteínas BMP-2, BMPR-IA, BMPR-II e endoglina - Araújo, Cristina Ruan Ferreira de (2009)
Bone morphogenetic proteins (BMPs) are cytokines involved in proliferation and angiogenesis of many kind of human cancer. The present study analyzed the immunohistochemical expression of BMP-2, BMPR-II, BMPR-IA and endoglin (CD105) and their relationship with the biological behavior and local angiogenesis in tongue oral squamous cells carcinoma (SCC). The sample consisted of 25 cases of tongue SCC without metastasis, 25 tongue SCC with metastasis and 25 cases of Inflamatory Fibrous Hyperplasia (IFH).The histological grade of malignancy proposed by Bryne (1998), adapted by Miranda (2002) was used to classify all tongue SCC cases. Score 0 was attributed to absent-weak immunoexpression and score 1 for strong immunostaning and pattern of distribution was focal or diffuse. Microvessel counts (MVC) was established for CD105. Most of the patients with tongue SCC was male. The principal age in tongue SCC without metastasis was over 65 years and in tongue SCC with metastasis was between 45-65 years. There were predominance of stage II in TNM and in the specimens with high-grade, independent of studied group. For BMP-2, 56% of tongue SCC without metastasis and 72% tongue SCC with metastasis exhibited score 1 while the IFH showed secore 0 in 72% of the cases, with statistical association (p=0,007). Considering the BMPR-II, 52% of tongue SCC without metastasis exhibited score 0; 56% tongue SCC with metastasis and 60% IFH showed score 1. The majority cases of BMPR-IA demonstrated score 1 and 100% of CD105 exhibited strong immunoexpression in tongue SCC. Regarding the pattern distribution, it was noted a tendency to diffuse pattern for the proteins in all groups. The means of MVC were similar in tongue SCC without metastasis (32,91) and in tongue SCC with metastasis (32,05), however existed statistical difference with IFH (p<0,001). There was statistical association of BMP-2 expression with BMPR-II (p=0,008), BMPR-IA (p=0,006) and CD105 (p=0,046). An association between TNM and BMP-2 immunoexpression and their receptors was not detected, nevertheless this association was found with MVC (p=0,047) whose averages were higher for the stages II (35,97) e IV (35,69). No association between histological grading and these proteins was observed. This study suggests that the superexpression of BMP-2 signaling pathways acts on cell proliferation in tongue SCC and can be implicated with more invasive potential. Additionaly, the CD105 is a potent biological marker of neovascularization in this neoplasm and their association with BMP-2 and BMPR-IA receptor, showed that this type of cancer in BMP-2 is presented as pro-angiogenic in the metastatic process